The traumatic effect of homicide in mentally disordered offenders and implications for treatment - Bromley, Alison (2016)
This thesis provides a broad and diverse investigation into the field of traumatic responses in mentally disordered perpetrators of homicide and group treatment for such offenders. A range of methods including a systematic review, a single case study and a primary phenomenological investigation were used to explore issues in the field. Following an introduction in Chapter 1, Chapter 2 reviews trauma responses in homicide offenders. The results indicate that trauma reactions among homicide offenders as a direct result of the offence are highly prevalent which has implications for potential interventions. The existing literature is obstructed by weak studies using suboptimal scientific designs and future research is recommended. In Chapter 3 a single case study explores a homicide offender’s progress in a group treatment. The group therapy under investigation adopts a recovery oriented approach, addressing both criminogenic need and the well-being of the offender. The impact of the treatment is determined using a range of psychometric measures. The results indicate improvements in the targeted areas with clinically significant change demonstrated. Chapter 4 explores the lived experience of a group treatment for homicide using the principles of Interpretive Phenomenological Analysis. Three areas were discussed: (1) the Group (2) Recovery and (3) Risk. Recurrent themes reflected the importance of shifting narratives and hope for the future in both domains of recovery and risk, lending support to the utilisation of narrative approaches in Index Offence work. The results have implications for clinical practice and are discussed in the context of directions for further research. Chapter 5 evaluates the Inventory of Complicated Grief which was used as an assessment measure in Chapter 3. Finally, Chapter 6 provides a discussion and close to the thesis drawing together the implications of the research.